2014
DOI: 10.1111/jop.12262
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analyses of Ki‐67, cytokeratin 13 and cytokeratin 17 in diagnosis and prognosis of oral precancerous lesions

Abstract: BACKGROUND: Ki-67, cytokeratin 13, and/or cytokeratin 17 detection by immunohistochemistry has been reported to be useful for the diagnosis of oral precancerous lesions. However, the use of these markers remains controversial because of the lack of appropriately designed statistical studies. We assessed the hypothesis that Ki-67, cytokeratin 13, or cytokeratin 17 immunohistochemistry could facilitate the diagnosis of oral precancerous lesions and/or predict prognosis. METHODS: Epithelial dysplasia was classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 35 publications
(71 reference statements)
2
45
0
Order By: Relevance
“…[71019] The previous literature on Ki-67 expression demonstrated the range of positivity for oral dysplastic epithelia from 13.5% to 51.2% and for oral SCC from 25% to 74.6%. [67891115] On the other end, many earlier studies and also this presently discussed study of ours have revealed that the lesions lacking any histopathological evidence of dysplasia may immunohistochemically express high and abnormal proliferative activity. [911] These OLs carry a significant potential to develop into SCC and should be managed in the same way as the corresponding grades of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[71019] The previous literature on Ki-67 expression demonstrated the range of positivity for oral dysplastic epithelia from 13.5% to 51.2% and for oral SCC from 25% to 74.6%. [67891115] On the other end, many earlier studies and also this presently discussed study of ours have revealed that the lesions lacking any histopathological evidence of dysplasia may immunohistochemically express high and abnormal proliferative activity. [911] These OLs carry a significant potential to develop into SCC and should be managed in the same way as the corresponding grades of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Yagyuu et al . [7] examined the OL patches from 94 Japanese patients and correlated the subepithelial lymphocytic infiltration with various grades of epithelial dysplasia as well as Ki-67 expression. They noticed that although there is an apparent tendency of higher subepithelial lymphocyte infiltration with increasing grades of dysplasia, such association did not manage any statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of CK13 along with expression of CK17 has been reported in (high-grade) oral epithelial dysplasia [1517]. Increased expression of CK17 has been reported for dVIN [14], but CK13 has not yet been explored for this lesion.…”
Section: Introductionmentioning
confidence: 99%